Water Productivity of Mustard Green (Brassica juncea L.) Under Drip Irrigation Systems and Organic Matter Addition - Nova Anika; Siti Mutmainah; Muhammad Kusmali; Harmiansyah Harmiansyah; David Septian Sumanto Marpaung; Ridwan Ridwan (The University of Lampung, 2025)
Drip irrigation technique, in combination with the utilization of organic matter like as biochar and cocopeat, can increase water productivity by tailoring irrigation water to plant demands. This study was to investigate how organic matter can improve water productivity in mustard green production utilizing a drip irrigation technique. The greenhouse pot experiment analyzes the effect of adding varying quantities of biochar and cocopeat to mustard greens' growth medium using a drip irrigation technique. The findings indicate that adding organic matter reduced the quantity of water needed for irrigation. The soil and biochar combination treatment at a 1:1 ratio resulted in the highest water productivity for mustard green, whereas the control treatment produced the least. Mustard green grows optimally in a soil + biochar (1:1) growing medium, yielding the most water productivity at 16.8 g/L. Biochar can boost biomass yield by twice as much as the control treatment. Furthermore, biochar can increase mustard green water productivity by more than 300% when compared to mustard green, which relies solely on soil for planting medium. Further study is needed to investigate the effects of biochar features on water holding capacity, field capacity, and wilting point in different soil types to improve irrigation efficiency. Keywords: Drip irrigation, Irrigation efficiency, Organic matters, Water productivity.